2020
DOI: 10.3390/jcm9072151
|View full text |Cite
|
Sign up to set email alerts
|

Epileptiform Discharge and Electrographic Seizures during the Hypothermia Phase as Predictors of Rewarming Seizures in Children after Resuscitation

Abstract: The aim of this study was to determine the frequency, timing, and predictors of rewarming seizures in a cohort of children undergoing therapeutic hypothermia after resuscitation. We retrospectively reviewed consecutive pediatric patients undergoing therapeutic hypothermia after resuscitation admitted to our pediatric intensive care unit between January 2000 and December 2019. Continuous electroencephalographic monitoring was performed during hypothermia (24 h for cardiac aetiologies and 72 h for asphyx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Twelve studies reported the relationship between absence or presence of seizures in children after cardiac arrest and good neurological outcomes at PICU/hospital discharge, 6 months, and 12 months. 175,188,189,191,198,199,[205][206][207][208][209][210] These studies included 1165 children, and 4 of the 12 studies reported using the ACNS criteria. 189,205,208,210 Absence of seizures up to 24 hours after ROC had a sensitivity of 50% to 100% with an FPR of 63% to 98% for predicting good neurological outcome at various time points.…”
Section: Absence Of Clinical or Electrographic Seizurementioning
confidence: 99%
See 4 more Smart Citations
“…Twelve studies reported the relationship between absence or presence of seizures in children after cardiac arrest and good neurological outcomes at PICU/hospital discharge, 6 months, and 12 months. 175,188,189,191,198,199,[205][206][207][208][209][210] These studies included 1165 children, and 4 of the 12 studies reported using the ACNS criteria. 189,205,208,210 Absence of seizures up to 24 hours after ROC had a sensitivity of 50% to 100% with an FPR of 63% to 98% for predicting good neurological outcome at various time points.…”
Section: Absence Of Clinical or Electrographic Seizurementioning
confidence: 99%
“…189,205,208,210 Absence of seizures up to 24 hours after ROC had a sensitivity of 50% to 100% with an FPR of 63% to 98% for predicting good neurological outcome at various time points. 191,205,208,209 Absence of seizure after 24 hours had a sensitivity of 50% to 100% with an FPR of 42% to 100% for predicting good neurological outcome. 175,188,189,191,198,199,202,208,210 Absence of Status Epilepticus Absence of status epilepticus was reported in 3 studies.…”
Section: Absence Of Clinical or Electrographic Seizurementioning
confidence: 99%
See 3 more Smart Citations